1986
DOI: 10.1136/jcp.39.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of mononuclear cell subsets in inflammatory and non-inflammatory myopathies.

Abstract: HospitalSUMMARY Immunohistochemical procedures were used to analyse the subpopulations of mononuclear cells in muscle biopsies from 24 patients with polymyositis. The character of the cellular infiltrate was similar at the perivascular, perimysial, and endomysial sites, with cytotoxic-suppressor T lymphocytes (T8 +) and macrophages being the dominant elements. Helper T lymphocytes (T4+) and B lymphocytes were present in smaller numbers. A control series of 17 muscle biopsies from normal subjects and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
3
7
0
2
Order By: Relevance
“…In fact, Engel and Arahata 24,25 described a PM pattern which is characterized by a progressive positive gradient fro CD8 + T cells from perivascular to endomysial region that was further confirmed by other investigators [26][27][28] .…”
Section: Discussionsupporting
confidence: 61%
“…In fact, Engel and Arahata 24,25 described a PM pattern which is characterized by a progressive positive gradient fro CD8 + T cells from perivascular to endomysial region that was further confirmed by other investigators [26][27][28] .…”
Section: Discussionsupporting
confidence: 61%
“…Estudos têm mostrado que biópsias musculares miopáticas ou neuropáticas podem conter pequeno número de linfócitos CD4+ e CD8+, com predomínio de linfócitos CD8+. Além disso, existem relatos da presença de células mononucleares ocasionais na biópsia muscular de pacientes sem doença neuromuscular, mas a importância desse achado ainda não foi determinada 9,11,47 . Também foram encontradas em nossos casos grande proporção de macrófagos no interstício, fibra necrótica perivascular na MCIC, nas miopatias distais e em um dos casos de distrofia muscular de cinturas em todos os locais examinados.…”
Section: Macrófagounclassified
“…Arahata e Engel também demonstraram que os macrófagos constituem elemento importante do infiltrado inflamatório da MCIC 9,10 . Os macrófagos são responsáveis pela fagocitose das fibras necróticas e talvez também tenham papel na patogênese da doença, já que são encontrados ao redor de fibras não necróticas, juntamente com linfócitos CD8+ 9,11,47 .…”
Section: Macrófagounclassified
“…A loss of the regulatory suppressor T lymphocytes from the peripheral blood in acute cases,2 similar to that found in multiple sclerosis,3 supports this view, while the analysis of the cellular infiltrates in affected muscle has started to reveal the characteristics of the immunological cells concerned.4 -9 Some workers have stressed the involvement of helper T cells,4 5 but others have concluded that cytotoxic-suppressor lymphocytes and macrophages are of most importance,69 with perhaps a local humoral effect also present in dermatomyositis. 6 The problem is compounded by finding the same inflammatory cells, in similar proportions, in inherited muscle diseases such as Duchenne dystrophy, and in non-inflammatory myopathies.6 8 In addition, the number of cases studied is still small, with very few patients from the different clinical subgroups or stages of the disease.…”
mentioning
confidence: 99%